Comparison Of Fentanyl And Clonidine In Attenuation Of Haemodynamic Response To Laryngoscopy And Endotracheal Intubation (Indian Journal of Applied-Basic Medical Sciences, 2021)
Background: Laryngoscopy and endotracheal intubation has led to provision of safer anaesthesia due to better  control of airway and ventilation. It is associated with reflex sympathetic stimulation resulting in an increase in  heart-rate and blood-pressure, which is known as pressor response to laryngoscopy and intubation. Various drugs have been used to avoid this pressor response. This study was aimed to assess the effects of IV  Fentanyl and IV Clonidine on pressor responses occurring due to laryngoscopy and intubation in normotensive  patients posted for a planned surgical procedure under general anaesthesia. Methods: Approval from the institutional ethical committee was taken for the study. We conducted this study in  60 patients belonging to ASA grade I and II, of 18 to 65 years of age, of either sex, scheduled for planned  surgical procedures under general anaesthesia. Patients were randomly allocated into 2 groups; the study drug was injected IV slowly 10 mins before induction. Group-F: received Inj Fentanyl 2mcg/kg Group-C: received Inj. Clonidine 2mcg/kg Observations were noted in terms of heart-rate, systolic-BP, diastolic-BP, mean-BP and spO2. Results: We observed that Clonidine pre-treatment provided better blunting of stress response during  laryngoscopy and intubation without causing clinically significant sedation, respiratory depression, bradycardia  or hypotension compare to Fentanyl. Conclusion: We came to a conclusion that Clonidine provided better response compare to Fenatanyl in obliterating the rise in  heart-rate and blood pressure on laryngoscopy and intubation.
Keywords: Laryngoscpoy; endotracheal intubation; pressor response; Clonidine; Fentany